Financialisation and market concentration in the USA: A monetary circuit theory - Ilhan Dögüs (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2021)
This paper explains the emergence of financialisation of nonfinancial corporations (NFCs) in the USA by way of the increased pension fund savings of white-collar workers which can be considered by Monetary Circuit Theory (MCT) as 'leakages' causing equity issuances to be replenished. The indirect causal nexus can briefly be explained that pension fund savings of white-collar workers have been facilitated by the increasing wage differential between white-collar and blue-collar workers which is driven by the increased market concentration. Since pension funds savings are channelled to financial markets instead of being spent for consumption goods, liquidity deficits of firms being replenished throughout stock markets and because of excess inflows into financial markets, profit expectations of NFCs from liquid financial assets have come to exceed the quasi-rent expectations from illiquid capital assets due to depressed demand for consumption goods. This paper stands as a reconstructive summary of findings of three published articles on each arguments of causal nexus and a contribution to MCT which has not yet considered market concentration.
Keywords: E44; J31; L1; 330; financialisation; market concentration; white-collar workers; wage differential; Monetary Circuit Theory